2020
DOI: 10.1523/jneurosci.2732-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Representation of Threat Features and Behavior in a Human Approach–Avoidance Conflict Anxiety Task

Abstract: Decisions under threat are crucial to survival and require integration of distinct situational features, such as threat probability and magnitude. Recent evidence from human lesion and neuroimaging studies implicated anterior hippocampus (aHC) and amygdala in approach-avoidance decisions under threat, and linked their integrity to cautious behavior. Here we sought to elucidate how threat dimensions and behavior are represented in these structures. Twenty human participants (11 female) completed an approach-avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Moreover, direct reciprocal connections between anterior HPC and the amygdala, insula, as well as medial PFC conspired to offer it a privileged interface with affect, especially anxiety and stress (Zeidman & Maguire, 2016). For example, human studies showed activation in the anterior HPC occurred in the paradigms like contextual fear conditioning (i.e., a spatial location associated with aversive stimulus; Pohlack, Nees, Ruttorf, Schad, & Flor, 2012), and approach‐avoidance conflict anxiety task which was central to the genesis of anxiety (Abivardi, Khemka, & Bach, 2020; Loh et al, 2017). Taken together, these findings indicated why it was the left rostral hippocamps, rather than its caudal zone, that anatomically functioned with the prefrontal regions to anxiety‐processing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, direct reciprocal connections between anterior HPC and the amygdala, insula, as well as medial PFC conspired to offer it a privileged interface with affect, especially anxiety and stress (Zeidman & Maguire, 2016). For example, human studies showed activation in the anterior HPC occurred in the paradigms like contextual fear conditioning (i.e., a spatial location associated with aversive stimulus; Pohlack, Nees, Ruttorf, Schad, & Flor, 2012), and approach‐avoidance conflict anxiety task which was central to the genesis of anxiety (Abivardi, Khemka, & Bach, 2020; Loh et al, 2017). Taken together, these findings indicated why it was the left rostral hippocamps, rather than its caudal zone, that anatomically functioned with the prefrontal regions to anxiety‐processing.…”
Section: Discussionmentioning
confidence: 99%
“…This is an example of accentuated alarm-to-threat stage by rigid binary cognitive strategy, whereas improving cognitive flexibility by configural associative learning could be a key element in the psychotherapeutical approach. Another example is that strong fear can elicit avoidance behavior related to the left lateral amygdala and anterior hippocampal hyperactivity (Abivardi et al, 2020). In other words, ''cold'' executive functioning is set to prioritize the most reliable decision-making to avoid danger when confronting a threat, yet it limits attention and flexibility.…”
Section: Alarm-to-threat (Check) Stagementioning
confidence: 99%
“…This tendency is reduced in persons with surgical and acute inflammatory hippocampus lesions [ 18 ]. Furthermore, gamma oscillations in HC and theta HC-PFC coupling increase with predator probability [ 33 ], and hippocampus (particularly CA2/3) BOLD signal increases with increased avoidance [ 39 ]. In N = 41 participants, self-reported trait anxiety [ 83 ] was related to behaviour in a non-linear way [ 40 ].…”
Section: Cross-species Anxiety Testsmentioning
confidence: 99%
“…Indeed, cross-species anxiety tests have led to remarkable insights into the basic neurobiology and cognitive mechanisms of threat avoidance behaviour in healthy individuals. Expanding on the classic septo-hippocampal model established in the 1980s [14,15], more recent research has highlighted the contribution of various additional brain regions to avoidance behaviour, such as amygdala [16][17][18], nucleus accumbens [19,20], area 25 [21], as well as striatum and anterior cingulate cortex (ACC) [22][23][24][25][26][27]; how they communicate by neural oscillations [28][29][30][31][32][33][34]; the more finegrained role of hippocampal subfields [35][36][37][38][39]; and the computational mechanisms that underly behaviour under threat [40][41][42][43] as well as their neural implementation [44]. Despite these fascinating insights, however, we argue that the field is yet to deliver on the three clinical promises.…”
Section: Introductionmentioning
confidence: 99%